2007
DOI: 10.2202/1542-0485.1186
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol: No Free Lunch

Abstract: The sharp rise in energy prices in the 1980s triggered a strong interest in the production of ethanol as an additional energy component. Economists are divided as to the payoffs from ethanol derived corn in part because of the complex interrelationship between energy produced from ethanol and energy from fossil fuels. Using a welfare economic framework, we calculate that there can be treasury savings from ethanol using tax credits as these subsidies can be smaller than direct payments to corn farmers which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 1 publication
3
20
0
Order By: Relevance
“…There are, however, several studies that consider important interactions between the tax code, renewable fuels mandates, and crop price supports (Gardner 2007;and Schmitz, Moss, and Schmitz 2007). Those studies find that the Renewable Fuel Standard (RFS) mandates are more effective than the tax incentives, and that the RFS effectively limited the impact of the tax incentives on renewable Beyond these studies, much of the literature focuses on whether ethanol production and consumption lead to a net increase or decrease in GHGs per Btu of fuel (Yacobucci and Bracmort 2010;Gelfand et al 2011).…”
Section: Existing Evidence On the Emissions Effects Of The Provismentioning
confidence: 99%
“…There are, however, several studies that consider important interactions between the tax code, renewable fuels mandates, and crop price supports (Gardner 2007;and Schmitz, Moss, and Schmitz 2007). Those studies find that the Renewable Fuel Standard (RFS) mandates are more effective than the tax incentives, and that the RFS effectively limited the impact of the tax incentives on renewable Beyond these studies, much of the literature focuses on whether ethanol production and consumption lead to a net increase or decrease in GHGs per Btu of fuel (Yacobucci and Bracmort 2010;Gelfand et al 2011).…”
Section: Existing Evidence On the Emissions Effects Of The Provismentioning
confidence: 99%
“…Accordingly, several studies have recently reported that the tax credit and mandated ethanol production increases the domestic fuel supply, leading to a reduction in the price of gasoline at the pump (Blanch, 2008;Cooper, 2008;de Gorter and Just, 2009b;Du and Hayes, 2008;Schmitz, Moss, and Schmitz, 2007). Blanch (2008) referenced a Merrill Lynch study indicating that conventional gasoline prices would be 15% higher without mandated ethanol production.…”
Section: Conventional Gasoline Productionmentioning
confidence: 99%
“…Du and Hayes (2008) reported that the growth in ethanol production has caused retail blended gasoline prices to be $0.29 to $0.40 per gallon lower than they would otherwise have been. Schmitz, Moss, and Schmitz (2007) reported that the increase in ethanol production lowers the price of gasoline by 4.3-6.0 cents per gallon, depending upon the relative size of the elasticity of demand for gasoline. The Renewable Fuels Association (2008a) summarized the impacts of ethanol on gasoline prices, claiming an ethanol savings ranging between $0.20 and $0.50 per gallon of gasoline.…”
Section: Conventional Gasoline Productionmentioning
confidence: 99%
See 2 more Smart Citations